Does all that is solid melt into air?: Questioning ’neo-liberal’ occult economies in Mozambique - Sumich, Jason (Kronos: Southern African Histories, 2017)
This article examines a scandal, concerning a foreign investor who was supposedly the head of an organ trafficking ring that broke out in the northern Mozambican city of Nampula in 2003. I use this scandal as a way to critique ideas of ’neo-liberal occult economies’. Instead of ’occult interpretations’ arising in an almost predetermined way as people revert to familiar idioms of sorcery to cope with their incomprehension at the changes wrought by neo-liberalism, I argue the Nampula organ scandal shows that it is people’s particular relationship to the state explains the scandal rather than simply economic changes. That is why this particular scandal ended up speaking far more convincingly to the fears of the better-off than of the poor.